З історії пам’яткоохоронної справи в Україні: питання культурної політики та збереження національної спадщини - Харковенко, Р.; Рішняк, О. (Український історичний журнал, 2021)
Мета дослідження – висвітлити історію й особливості формування сфери охорони
культурної спадщини України. Методологія полягає у застосуванні методів історизму, системності, загальнонаукових методів логіки, компаративного аналізу, спеціально-історичних методів
(історіографічного аналізу, ретроспективного аналізу, хронології, історико-системного, історико-генетичного, порівняльно-історичного). Наукова новизна. З’ясовано історичні витоки й чинники формування пам’яткоохоронної галузі України, питання культурної політики і збереження національної спадщини. Висновки. Питання формування дієвої та ефективної системи охорони
культурної спадщини, яка становить основу й запоруку обліку, охорони, збереження її об’єктів
і пам’яток, нагальне. Необхідно спрямувати спільні зусилля органів державної влади, місцевого
самоврядування, науковців, громадськості на його вирішення. Держава зобов’язана розглядати
національну культурну спадщину в контексті культурної політики як стратегічний ресурс країни. Вирішення наявних проблем слід розпочинати з розробки виразної стратегії та розв’язання
пріоритетних завдань. Адже на сьогодні надзвичайно актуальне питання щодо необхідності створення результативної й ефективної системи органів державної влади у сфері охорони культурної
спадщини з чітко визначеними повноваженнями, як це передбачено законом України «Про охорону культурної спадщини» (2000 р.). Україна є країною з високим рівнем духовності громадян, який визначається їхнім ставленням до культурних надбань минувшини. Залишені у спадок від
попередніх поколінь історичні релікти – підвалина розвитку культури нашої держави й людства
загалом. За всієї самобутності українська культурна спадщина становить собою невід’ємну складову світового культурного надбання, яка викликає широкий інтерес у міжнародної спільноти. The purpose of the study is to show the specifics of the formation of the modern area of
cultural heritage protection of Ukraine. The methodology consists in the application of methods
of historicism, systematicity, general scientific methods of logic, comparative analysis, special-historical
methods (historiographical analysis, retrospective analysis, chronology, historical-systemic, historicalgenetic,
comparative-historical). Scientific novelty. The historical origins and factors of formation
of the monument protection branch of Ukraine were investigated. Today there is a rethinking of
the role and place of cultural heritage in the life of society and in the life of a particular person. Today,
Ukraine is in a state of self-determination, as it is experiencing the effects of globalization, the signs of
which appeared several decades ago. The result is a clear decline in the level of culture of the main
groups of the population and as a result – insufficient level of attention and care for cultural heritage.
Conclusions. It should be noted that the issue of creating an effective and efficient system of cultural
heritage protection has long been ripe in Ukraine. After all, this system is the core, basis, foundation and
guarantee of accounting, protection and preservation of cultural heritage objects and monuments of
Ukraine. In our opinion, today it is necessary to direct all efforts of public authorities, local governments,
scientists and the public to address this issue. It directly affects the extent to which and to what condition
we will pass on cultural heritage sites to future generations. The state should consider the national
cultural heritage in the context of cultural policy as a strategic resource of the country. Addressing
existing issues should begin with developing a strategy and addressing priorities. After all, today the issue
of the need to create an effective and efficient system of public authorities in the field of cultural heritage
protection with clearly defined powers, as provided by the Law of Ukraine “On Cultural Heritage
Protection” is extremely relevant. Ukraine was and remains a country with a high level of spirituality of
citizens, which is determined by their attitude to the cultural heritage of the past. The historical relics
inherited from previous generations are the basis for the development of the national culture of the
people and humanity in general. For all its originality, the Ukrainian cultural heritage is an integral part of
the world cultural heritage, which is of interest to the international community.